Expanding pedological maps to physiographically similar areas with digital soil mapping - Bagatini, Tatiane; Giasson, Elvio; Teske, Rodrigo (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to expand pedological maps by extrapolating existing soil maps to physiographically similar areas. Soil maps were used at the scale of 1:50,000, for the watersheds of the rivers Santo Cristo and Arroio Portão, in the state of Rio Grande do Sul, Brazil, and the extrapolation was done using the “Simple Cart” decision tree algorithm, trained in the previously mapped areas. The watersheds were divided into two parts, one used for model training and the other for model validation. From the digital elevation model Aster-GDEM, seven maps of soil predicting variables in the landscape were generated. Sampling was random and performed with sampling density of three points per hectare. Model training was performed in the Weka software, and model accuracies were calculated using the error matrix. For both watersheds, the overall accuracy of the predicted soil map was higher in the training area than in the validation area, and showed values of 50 and 54%. The maps produced by the predictive model showed acute differences in the spatial distribution of mapping units, compared with the original soil map, indicating that the used digital mapping technique has low effectivity for the extrapolation of pre-existing soil maps to other physiographically similar areas.